THE LONGMIRE PROCEDURE: IS IT WORTHWHILE? - Aurangzeb, Mehmood (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the peripheral intrahepatic cholangiojejunostomy (Longmire procedure) for the palliative treatment of jaundice in patients with irresectable malignant tumours of the liver hilum. Material and Methods: In a retrospective study, indications, surgical technique, perioperative complications, and efficacy of treatment were analyzed for 17 patients who had received a Longmire peripheral intrahepatic cholangiojejunostomy between May 2000 and August 2004. Results: The Longmire procedure was exclusively palliative in all 17 cases. The 30-day mortality in the study group was 11.6% (n=2/17), and the mean survival was 6.2 months. In patients surviving more than one month, a marked and persistent decrease in cholestasis was achieved in 86.6% cases. Conclusion: The Longmire peripheral intrahepatic cholangiojejunostomy is a feasible and a worthwhile procedure and offers a reasonably effective palliative treatment for patients with irresectable tumours of the liver hilum.